On the Cultural Peculiarities of Proverbs and Their Classification - Gevorgyan, Kristine (Armenian Folia Anglistika, 2009)
Recent observations of the interrelation between language and culture guided scholars to the sphere of Paremiology. Making up a specific layer of the word stock, proverbs contain valuable information about national traditions and worldview.Proverbs can be found in all languages and they have been investigated from different perspectives.The present article attempts to illustrate the paremiological expressions and classify them in the system of the language and culture.